2018
DOI: 10.1016/j.omtm.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Viral Platform for Intramuscular Passive Vaccine Delivery to Human Skeletal Muscle

Abstract: Skeletal muscle is ideal for passive vaccine administration as it is easily accessible by intramuscular injection. Recombinant adeno-associated virus (rAAV) vectors are in consideration for passive vaccination clinical trials for HIV and influenza. However, greater human skeletal muscle transduction is needed for therapeutic efficacy than is possible with existing serotypes. To bioengineer capsids with therapeutic levels of transduction, we utilized a directed evolution approach to screen libraries of shuffled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…The cost and time of the screening process can be minimized by predeterming the appropriate MOI and number of selection rounds for a particular screen. For previous library screening studies in our lab that did not employ barcoded libraries, four or more rounds of selection were routinely performed (Grimm et al, 2008;Lisowski et al, 2014;Paulk et al, 2018a;Paulk et al, 2018b). However, in the current study, we found that three rounds of selection were sufficient to enrich and amplify variants with improved transduction of the target cell type to a level where they could be isolated reliably.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cost and time of the screening process can be minimized by predeterming the appropriate MOI and number of selection rounds for a particular screen. For previous library screening studies in our lab that did not employ barcoded libraries, four or more rounds of selection were routinely performed (Grimm et al, 2008;Lisowski et al, 2014;Paulk et al, 2018a;Paulk et al, 2018b). However, in the current study, we found that three rounds of selection were sufficient to enrich and amplify variants with improved transduction of the target cell type to a level where they could be isolated reliably.…”
Section: Discussionmentioning
confidence: 99%
“…While the possibility of cross-packaging, which is characterized by sequence differences between the packaging capsid and the corresponding viral genome, cannot be excluded, several of the enriched capsids from our screen were found to exhibit the desired phenotype, suggesting that cross-packaging or mosaicism was not a major problem in our libraries. Moreover, when we had previously generated AAV libraries using high concentrations of AAV plasmid during transfection, we had been successful in generating variants with greatly improved phenotypes (Grimm et al, 2008;Lisowski et al, 2014;Paulk et al, 2018a;Paulk et al, 2018b), suggesting that for reasons unknown so far there seems to be a strong capsid genotype linkage in case of AAV packaging (Grimm & Zolotukhin, 2015). A recent report by the Grimm group laid to rest the concern that functionality of AAV capsid libraries generated for directed evolution studies might be severely compromised by inactivation of the assembly activating protein (AAP) in a large proportion of the chimeric variant pool (Herrmann et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether these potency differences were restricted to IM delivery of rAAV1, we repeated the same experiment with rAAV8-a serotype currently being tested as an intramuscular HIV passive vaccine vector 33 , despite reports of poor transduction in human skeletal muscle 34 and other human tissues 35,36 , as well as high neutralizing antibody levels in HIV+ individuals 37 . Here again, twelve mice (6 male and 6 female) were injected IM with 5e10 vg of ssAAV8-CMV-FLuc vector and liveimaged weekly for FLuc expression (Figures 3f, S13c).…”
Section: Vectors Produced By Different Manufacturing Platforms Differmentioning
confidence: 99%
“…Administration of rAAV IM is typically only done when treating muscle disorders or when using muscle as a secretion depot for passive vaccines 34 . Many gene therapy trials administer vector intravenously (IV) to facilitate distribution to internal organs not easily accessible by direct injection.…”
Section: Raav Vectors Exhibit Significant Sexually Dimorphic Functionmentioning
confidence: 99%